공공갈등해결의 영향요인 분석 - 황창호; Hwang Changho; 이남국; Lee Nam-kuk (한국거버넌스학회보, 2019)
우리 사회에서 일어난 많은 공공갈등은 심화, 증폭, 연계, 대상의 불명확성과 같은 특성을 보여왔다. 이로 인해 공공갈등을 효과적으로 관리하고 해결하고자 하는 실질적인 대책을 마련하는 노력이 이어져왔다. 그러나 공공갈등 해결의 중요성에도 불구하고 이와 관련한 연구는 그리 많이 이루어지지 않았다. 따라서 이러한 한계를 극복하기 위하여 이 연구에서는 공공갈등해결에 중요한 선행변수인 조직요인, 인적요인, 법제도적요인, 사회문화적요인, 시민참여적요인 변수를 중심으로 공공갈등해결과의 상호연계성을 살펴보았다. 분석결과를 요약하면 공공갈등해결에는 법제도적요인과 사회문화적요인이 통계적으로 유의미한 영향을 미치는 것으로 나타났다. 반면에 조직요인과 인적요인 그리고 시민참여적요인은 통계적으로는 공공 갈등해결에 아무런 영향을 미치지 않는 것으로 나타났다. 이는 갈등전담기구, 갈등전문인력, 시민참여적 요인 또한 갈등해결을 위해 중요한 변수임에는 틀림없지만 무엇보다 다양한 이해관계자들이 서로의 가치를 인정하고 존중할 줄 아는 사회문화적 환경의 조성과 갈등 관련한 합리적인 보상체계 및 전반적인 갈등 해결 위한 법적프로세스가 체계적으로 구축될 때 공공갈등이 보다 원만하게 해결될 수 있음을 시사한다. Many public conflicts in our society have been characterized by deepening, amplification, linkage, and ambiguity of objects. As a result, efforts have been made to provide practical measures to effectively manage and resolve public conflicts. However, in spite of the importance of solving public conflict, much research has not been done on it. Therefore, in order to overcome these limitations, this study examined the interconnectivity of public conflict resolution, focusing on organizational factors, human factors, legal institutional factors, socio-cultural factors, and civic participation factors. The results of the analysis show that legal institutional factors and sociocultural factors have a statistically significant impact on public conflict resolution. On the other hand, organizational factors, human factors, and citizen participation factors have no statistically significant impact on public conflict resolution. This is because it is essential for conflict resolution, conflict experts, and civic participation in the conflict resolution process. However, it is necessary to establish a socio-cultural environment in which various stakeholders recognize and respect each other's values, Suggests that public conflicts can be solved more smoothly when the legal process for resolving the overall conflict is systematically established.